Consensus and controversy in the discipline of invasion science - Ross T. Shackleton; Giovanni Vimercati; Anna F. Probert; Sven Bacher; Christian A. Kull; Ana Novoa (Conservation Biology, 2022)
Approaches, values, and perceptions in invasion science are highly dynamic, and like in other disciplines, views among different people can diverge. This has led to debate in the field specifically surrounding the core themes of values, management, impacts, and terminology. Considering these debates, we surveyed 698 scientists and practitioners globally to assess levels of polarization (opposing views) on core and contentious topics. The survey was distributed online (via Google Forms) and promoted through listservs and social media. Although there were generally high levels of consensus among respondents, there was some polarization (scores of ≥0.39 [top quartile]). Relating to values, there was high polarization regarding claims of invasive species denialism, whether invasive species contribute to biodiversity, and how biodiversity reporting should be conducted. With regard to management, there were polarized views on banning the commercial use of beneficial invasive species, the extent to which stakeholders’ perceptions should influence management, whether invasive species use alone is an appropriate control strategy, and whether eradication of invasive plants is possible. For impacts, there was high polarization concerning whether invasive species drive or are a side effect of degradation and whether invasive species benefits are understated. For terminology, polarized views related to defining invasive species based only on spread, whether species can be labeled as invasive in their native ranges, and whether language used is too xenophobic. Factor and regression analysis revealed that views were particularly divergent between people working on different invasive taxa (plants and mammals) and in different disciplines (between biologists and social scientists), between academics and practitioners, and between world regions (between Africa and the Global North). Unlike in other studies, age and gender had a limited influence on response patterns. Better integration globally and between disciplines, taxa, and sectors (e.g., academic vs. practitioners) could help build broader understanding and consensus.